Operating Systems for Mobiles until late 2018: A Comparative Survey and Overview - Prathap, Boppuru Rudra (International Journal of Computer Sciences and Engineering, 2018)
Smart phones and other latest technologies have been, and continue to be emerging in today’s world. The same has been observed to be showcased by the operating systems that supplement each of the said technologies. There are multiple operating systems available today and some of the select operating systems have been made compatible across various devices. For instance, macOS developed by Apple Inc for their lineup of Mac products can synchronize seamlessly with the iOS for other products from the same manufacturer while still promoting collaboration between their phone and laptop lineups. A universal platform was proposed by Microsoft to function across their range of laptops and smart phones. Also, Android which began for smart phones has now been extended to its own version for automobiles. At the same time, there are millions of new releases, both familiar and unfamiliar directed towards dominating the market today. All of these advancements raise questions as to which operating system is to be relied upon and for which application has the ability to outperform one another. This paper is dedicated specifically towards mobile operating systems employed by leading manufacturers followed by a parallel analysis of the same.